Przegrana wojna czy przegrana rewolucja? Próba parafrazy kontrowersji wokół mechanizmów demokratyzacji społeczeństw zachodnich w socjologii historyczno-porównawczej - Brzechczyn, Krzysztof (Księgarnia Akademicka, 2010)
It is maintained – mostly in the leftist social thought – that the victorious revolution are optimal method of social change leading to desired social order. The domination of normative dimension over the descriptive one in this kind of social reflection caused that the examples of revolutionary despotism is often overlooked. This problem can be properly posed in such kind reflection on revolution in which descriptive dimension is clearly distinguished from the normative one. This is a case of theories of revolution formulated in historical comparative sociology. The aim of this essay is critical examination of approaches on consequences of revolutions and mechanisms of democratization developed by Jack A. Goldstone, Ted Robert Gurr, Erich Weede, and Edward N. Muller. The critical analysis reveals some their flaws and disadvantages. The paraphrase of mentioned-above theories in notion apparatus of Leszek Nowak’s theory of power in non -Marxian historical materialism allows for their explication and – in some cases – further extension.
Keywords: socjologia historyczno-porównawcza; nie-Marksowski materializm historyczny; demokratyzacja; rewolucja; comparative historical sociology; non-Marxian historical materialism ro; democratization; revolution